Trimethyl-, triethyl- and trimethoxybenzene-based tripodal compounds bearing pyrazole groups: conformations and halogen-/hydrogen-bond patterns in the crystalline state. Issue 27 (29th June 2017) - Koch, Niklas; Seichter, Wilhelm; Mazik, Monika
Abstract : X-ray analyses of a series of benzene-based tripodal molecules1–9 provide interesting insights into the molecular recognition phenomena and give information about the different conformations which adopt the molecules in the solvent-free crystals and in solvates. Abstract : X-ray analyses of a series of benzene-based tripodal molecules1–9, bearing either bromo-substituted pyrazole groups or analogues lacking the bromo substituents, provide interesting insights into the molecular recognition phenomena and also give information about the different conformations which adopt the tripodal molecules in the solvent-free crystals and in solvates. The crystal packings are characterized by the presence of C–H⋯O, C–H⋯N, C–H⋯Br and C–H⋯Cl hydrogen bonds as well as C–Br⋯N, C–Br⋯Br, C–Br⋯Cl and C–Br⋯π halogen bonds. The conformations observed in the case of the triethyl- and trimethoxybenzene-based compounds can be defined as ab'ab'ab', ab'ab'ba', ab'ab'bb', ab'aa'ba', ab'aa'bb', aa'ab'ba' and aa'aa'aa' with the pyrazole-bearing arms arranged either in an aaa or an aab fashion.